Ett liv värt att leva: före detta patienters upplevelse av förändring efter DBT inom BUP - Jimson,Johanna; Lindahl,Anne (2013)
The study aims to investigate whether former patients experience that DBT-treatment in a child and adolescent psychiatric clinic has helped them in building a life worth living. Semi-structured interviews were conducted with eight women aged 17-22 years who had undergone DBT treatment one to three and a half years ago. The data were analyzed using Interpretative Phenomenological Analysis (IPA), which is based on phenomenological and hermeneutic theory. The analysis resulted in six main themes; Suffering, To live – not just survive, To be something more, Meaningful relationships, To be able to look forward and Other contributing factors to a ”life worth living”. Most participants experience DBT as helpful in building a life worth living, albeit to different degrees. The treatment has brought a positive change in a number of areas which include becoming better at identifying and regulating emotions, having a greater understanding of oneself, and improving relationships with others. The participants’ experience was that they could deal with everyday life in a more constructive way, their self-harming behaviors have ceased or decreased considerably.
Keywords: dialektisk beteendeterapi; ungdomar; ett liv värt att leva; självskadebeteende; emotionsreglering; relationer; kvalitativ studie; IPA